Distribution record of Musa borneensis var. sarawakensis Becc. and Musa campestris var. sarawakensis Becc. in West Kalimantan, Indonesia - Ari Sunandar; Arif Didik Kurniawan (Journal of Tropical Biodiversity and Biotechnology, 2020)
Borneo Island has a large number of wild banana species. As a part of Borneo Island, West Kalimantan has limited information about the diversity of wild bananas. This research aims to update the record distribution of wild bananas from Bonti District of Sanggau Regency and to determine their morphological characteristics. Exploration method and resident information were used in this study. Two species of wild bananas have been identified and considered as new distribution records in West Kalimantan Province, namely-Musa borneensis var. sarawakensis with morphological character pseudostem red-purple colour, sparse black-purple blotches at petiole base, leaf base shape rounded on both sides, male bud red-purple colour and Musa campestris var. sarawakensis with morphological character pseudostem yellow-green colour, inflorescence erect, leaf base one side rounded and one-pointed, the dorsally pink-purple and ventrally pink-purple colour of bract.